The Effect Of Concurrent Position And Tenure Of President Director And Ownership Structure On Environmental, Social, And Governance (ESG) Value - Hafika Prafiani; Cynthia Afriani Utama (UNIVED Press, 2024)
The decision on how much the company contributes to environmental, social, and governance (ESG) related activities is influenced by President's characteristics and the company ownership structure. Present study was undertaken to investigate the effects of the President's busyness and tenure, as well as the ownership structure of family companies, on the ESG scores of companies in Indonesia. The present study used 221 observations from 50 companies listed in the Indonesia Stock Exchange and Refinitiv ESG Scores database from 2016 – 2020 and analyzed them by the Regression method. The findings suggested that companies that have busy presidents or CEOs and family ownership structures give low ESG scores. While the authors do not find sufficient evidence to support the President Director serving more than five years has a good influence on ESG scores. It is because family companies tend to focus on enriching their families. Companies can limit the number of concurrent positions held by the President and recruit a President who has extensive experience. This study contributes to investigating the correlation between ESG scores with the President's concurrent positions and the company ownership structure.